High-Quality Exome Sequencing of Whole-Genome Amplified Neonatal Dried Blood Spot DNA - Poulsen, Jesper Buchhave; Lescai, Francesco; Grove, Jakob; Bækvad-Hansen, Marie; Christiansen, Michael; Hagen, Christian Munch; Maller, Julian; Stevens, Christine; Li, Shenting; Li, Qibin; Sun, Jihua; Wang, Jun; et al. (PLOS ONE, 2016)
Stored neonatal dried blood spot (DBS) samples from neonatal screening programmes are a valuable diagnostic and research resource. Combined with information from national health registries they can be used in population-based studies of genetic diseases. DNA extracted from neonatal DBSs can be amplified to obtain micrograms of an otherwise limited resource, referred to as whole-genome amplified DNA (wgaDNA). Here we investigate the robustness of exome sequencing of wgaDNA of neonatal DBS samples. We conducted three pilot studies of seven, eight and seven subjects, respectively. For each subject we analysed a neonatal DBS sample and corresponding adult whole-blood (WB) reference sample. Different DNA sample types were prepared for each of the subjects. Pilot 1: wgaDNA of 2x3.2mm neonatal DBSs (DBS_2x3.2) and raw DNA extract of the WB reference sample (WB_ref). Pilot 2: DBS_2x3.2, WB_ref and a WB_ref replica sharing DNA extract with the WB_ref sample. Pilot 3: DBS_2x3.2, WB_ref, wgaDNA of 2x1.6 mm neonatal DBSs and wgaDNA of the WB reference sample. Following sequencing and data analysis, we compared pairwise variant calls to obtain a measure of similarity—the concordance rate. Concordance rates were slightly lower when comparing DBS vs WB sample types than for any two WB sample types of the same subject before filtering of the variant calls. The overall concordance rates were dependent on the variant type, with SNPs performing best. Post-filtering, the comparisons of DBS vs WB and WB vs WB sample types yielded similar concordance rates, with values close to 100%. WgaDNA of neonatal DBS samples performs with great accuracy and efficiency in exome sequencing. The wgaDNA performed similarly to matched high-quality reference—whole-blood DNA—based on concordance rates calculated from variant calls. No differences were observed substituting 2x3.2 with 2x1.6 mm discs, allowing for additional reduction of sample material in future projects.